The Role of Religious Leaders in Lessening Stigma Toward Individuals with HIV/AIDS in Islamic Communities of Cirebon City - Muslimin, Muslimin; Ladid, Rifki Fata; Hikhmat, Rokhmatul; Herawati, Cucu; Shobihuddin, Syifa Hidayat (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to examine the contribution of religious leaders in reducing stigma against PLWHA within Muslim communities in Cirebon City. The research employed a qualitative phenomenological method to capture the lived experiences of religious leaders, PLWHA, and other stakeholders. Data were collected through in-depth interviews, participatory observation, and documentation conducted between March and May 2025. In total, 12 religious leaders, 10 PLWHA, three healthcare officers, and representatives from 2 local NGOs participated in the study. Observations were carried out in mosques, religious study groups, and health institutions across Cirebon City to understand the real practices of inclusive preaching and collaboration. The data were analyzed using the Colaizzi phenomenological approach, which involved identifying significant statements, formulating meanings, clustering themes, and validating findings through member checking. The research findings indicate that the presence of religious leaders plays a significant role in shaping a more open public view of PLWHA. Through an inclusive religious approach based on humanitarian values, religious leaders can act as drivers of social change that strengthen solidarity and eliminate the stigma inherent in PLWHA. Therefore, this study recommends the need for skills development and capacity building programs for religious leaders so that they can play an optimal role in efforts to eliminate HIV/AIDS stigma within Muslim communities.